PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR FISIKA PADA POKOK BAHASAN BESARAN DAN SATUAN SISWA KELAS X IIS 2 SMA NEGERI 1 PUPUAN TAHUN PELAJARAN 2018/2019 - Suarma, I Wayan (LPPM IKIP PGRI Bali, 2019)
The Purpose of this research is to increase the student's achievement through applying of learning model called group investigation in learning physics. Kind of this research is classroom action research. The subject of this research is students of X IIS 2 SMA Negeri I Pupuan at first semester year 2018/2019 which consist of 21 students. This research is done in two cycles of learning with some steps which every cycle follows the learning step of group investigation The data of the student's achievenent is collected through the evaluation activity (quiz), assignment, and the result of the test at every cycle. The data which has collected, futhermore, is analysed in descriptive way. The data of analysed result after modeling of group investigation learning is implemented by the average of student's achievement of firts cycle in the omount of 81,47 by total clasical is in the amount of 86%. The average of student's achicvement at second cycle is in the amount of 81,47 by total clasical is in the amount of  95%. From the result above, it can be concluded that the application of learning model group investigation can increase the achievement of students in learning physics for students ? IS 2 SMA Negeri 1 Pupuan al first semester of year 2018/2019.